Euro adoption and intra-European Union exporters' productivity: Differences between family and non-family firms - Rodrigo Basco; Thomas Bassetti; Fernando Mu\~noz-Bullón; Maria J. Sanchez-Bueno (European Research on Management and Business Economics (ERMBE), 2023)
How do exporters react to changes in formal institutional contexts? We hypothesise that when the formal institutional context reduces uncertainty, family-firm exporters increase their productivity more than those of non-family firms. To examine our general conjecture empirically, we leveraged the shift from a flexible to a fixed exchange rate regime that occurred with the adoption of the euro. Our findings showed that, after adopting the euro, intra-European Union (EU) family-firm exporters achieved higher productivity than non-family-firm exporters. Owing to the elimination of exchange rate volatility, intra-EU family-firm exporters, who were particularly sensitive to uncertainty because of their specificities related to wealth concentration, family-oriented goals, and corporate transparency, became more willing to adopt investment decisions than intra-EU non-family-firm exporters. Consequently, these investments yielded significant improvements in the productivity levels of the former group. We also found that the gains in productivity were not evenly distributed among intra-EU family-firm exporters. The introduction of the euro facilitated the transition of intra-EU family-firm exporters from low to intermediate productivity levels. Moreover, it allowed those with initially intermediate productivity levels to remain in the same group, while reducing the likelihood of falling behind high-productivity intra-EU family-firm exporters.
Keywords: L60; L20; 650; Family firm; Total factor productivity; Export; European Union; Internationalisation